计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 08:29:40
计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x原式=3x-4y+(
计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x
计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x
计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x
原式=3x-4y+(2y+x)-(x-3y)-6x
=-3x-4y+(2y+x)-(x-3y)
=-3x-4y+2y+x-x+3y
=-3x+y
(3x-4y)-[-(2y+x)+(x-3y)]-6x
=3x-4y+(2y+x)-(x-3y)-6x
=3x-4y+2y+x-x+3y-6x
=(3x+x-x-6x)-(4y-2y-3y)
=-3x+y
计算:(3x-4y)-[-(2y+x)+(x-3y)]-6x
计算(x-y)^2×(x-y)^3×(y-x)×(y-x)^2
计算:[(x+y)³-2(x+y)²-4(x+y)]÷(x+y)
(4x^2y+x^3y^3)÷(-2x^2y)计算
计算 (-x+y)∧4×(x-y)∧2×(y-x)∧3
(x-2y)(x+y)+(x+y)计算
计算:(x-y)^2-(x+y)(x-y)
计算:(3x+4y)(3x-4y)-5(x+y)(x-2y)
计算 x-2分之x方+1-2-x分之3-4x (x+y)x方-y方分之x方+y-x分之y方
因式分解(-x-2y)(3x-y)计算
(x+y)^2-(3x-2y)^2计算
计算x^2y^-3(x^-1y)^3
计算:(x-3y)(x+2y)
-2x(3x-7y)+(x-y)(x^2+xy+y^2) 计算
计算:(1)8x^2y^2*(-3x/4y^5) (2)(x+y)^2/xy-y^2*(y-x)^2/xy+y^2
计算-{-[-(3x-y)]}
计算:-x-3(x-y)+4(x-2y)
计算(1)x/x+y-x/x-y (2)a+2+4/a+2 (3)x^2-y^2/xy÷(x+y)